Vigorous-intensity exercise as a modulator of cardiac adipose tissue in women with obesity: a cross-sectional and randomized pilot study - Thapa, Sumsen; Selvaraj, Bharath S.; Davis, Paige N.; Smith, Bryan; Givan, Amy H.; Perez-Rivera, Jose A.; Woodard, Pamela K.; Klingensmith, Jon D.; Fernandez-del-Valle, Maria (Frontiers in Endocrinology, 2023)
This study aims to analyze the relationships between cardiac adipose tissue (CAT), physical activity (PA), and physical fitness (PFit) in women with obesity and explore the effects of different exercise modalities. A total of 26 women (age: 23.41±5.78 years-old) were enrolled in the cross-sectional study. PA, cardiorespiratory fitness, muscular strength, body composition and CAT were evaluated. The pilot intervention included 16 women randomized to a control (CON, n=5), high intensity interval training (HIIT, n = 5) and high-intensity circuit training (HICT, n=6) groups. Statistical analysis showed negative correlations between CAT and vigorous PA (VPA) (rs=-0.41, p=0.037); and between percent body fat (%BF), fat mass (FM), and all PA levels (rs=-0.41– -0.68, p<0.05); while muscle mass was positively associated with moderate-to-vigorous PA, and upper-body lean mass with all PA levels (rs =0.40–0.53, p<0.05). The HICT intervention showed significant improvements (p<0.05) in %BF, FM, fat free mass, and whole-body and lower extremities lean mass and strength after three weeks; however, only leg strength and upper extremities’ FM improved significantly compared to CON and HICT. In conclusion, although all types of PA showed a positive influence on body fat content, only VPA significantly impacted on CAT volume. Moreover, three weeks of HICT induced positive changes in PFit in women with obesity. Further research is needed to explore VPA levels and high-intensity exercise interventions for short- and long-term CAT management.